Penggunaan Media Pembelajaran Berbasis E-Learning Pada Mata Pelajaran Pendidikan Agama Islam di Sekolah - Rina Khoridah (CV Putra Publisher, 2023)
The study aims to examine how to use and what are the supporting and inhibiting factors for E-learning learning media used in PAI subjects. This research uses a quantitative approach with a quantitative descriptive method. The results showed that in its implementation, teachers delivered material in the form of text and video via Whatsapp and Google Classroom while the evaluation of PAI learning was carried out by giving questions to students through Google Form, with the results that a percentage of 58.1% of students could understand jurisprudence learning delivered through E-learning-based media. Although students understand the material, as teachers must still strive so that the evaluation process can run well, because in research it was found that around 10.3% Students strongly agree to freely cheat, as for the supporting factor in the use of E-learning, namely IT mastery that must be owned by every teacher, in this case the school holds an In House Training program related to online learning. Meanwhile, obstacles in the implementation of PAI learning are signals and economic conditions of parents.